The Effect of Giving Boiled Water of Star fruit Wuluh (Averrhoa Bilimbi L) on Blood Decrease in Hypertension Patients at Pusong Lama Banda Sakti Lhokseumawe - Alhuda; Fatmawati (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2021)
The control and improvement of hypertension sufferers are increasing every year because of the highest cost of medicines relatively and lifestyle changes. It’s needed special treatment as an alternative to getting medicine in order to decrease the number of hypertension cases and also be overcome by using herbal medicine, namely boiled water star fruit. The purpose of this study was to determine the effect of giving boiled water of star fruit Wuluh on reducing blood pressure in patients with hypertension in Pusong Lama Village, Banda Sakti District, Lhokseumawe City in 2018. This study used a quasi-experimental style with a one-group pretest-posttest style while not a sway cluster. Sampling is taken by purposive sampling as several as twenty-five individuals. The analysis is employed the t-dependent check (paired t-test). In the t-dependent take a look at (paired t-test) it had been found that there was a way of giving stewed water carambola Wuluh (Averrhoa Averrhoa bilimbi L) on the pressure in patients with high blood pressure in Pusong Lama Village, Banda Sakti District, Lhokseumawe with p-value = 0.000 or count table (9.252 1.711) on systolic blood pressure while on the diastolic blood pressure variable. It is known that t-count table (7.856 1.711) or p (value) = 0.000<0.05. Based on the results of this study, it is all over that there's a major and powerful impact when giving stewed water carambola (Averrhoa Averrhoa bilimbi L) on reducing pressure in hypertensive patients in Pusong Lama Village, Banda sakti District, Lhokseumawe. It is recommended to those with hypertension to reduces the risk of hypertension by using herbal medicines, one of which is by using boiled water star fruit where the costs relatively cheap and it is recommended to do regularly checking their blood pressure to avoid the risk of stroke.